Synthesis of Functionalized Adamantane Derivatives: (3 + 1)-Scaffolds for Applications in Medicinal and Material Chemistry - Fleck, Carsten; Franzmann, Elisa; Claes, Dorith; Rickert, Aljona; Maison, Wolfgang (Synthesis, 2013)
Due to its rigid cage structure, adamantane has received considerable interest as a scaffold with a defined tetrahedral geometry. In this paper we describe orthogonally functionalized tetrasubstituted adamantane derivatives. These compounds may be conjugated to other functional molecules by standard techniques such as amide formation or click chemistry and are thus useful (3 + 1) scaffolds for medicinal and material chemistry.
Keywords: adamantane; multivalency; dendrimers; C3 symmetry; diamandoids